2014
DOI: 10.1093/jxb/ert447
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid is an indispensable component of the Ny-1 resistance-gene-mediated response against Potato virus Y infection in potato

Abstract: The purpose of the study was to investigate the role of salicylic acid (SA) signalling in Ny-1-mediated hypersensitive resistance (HR) of potato (Solanum tuberosum L.) to Potato virus Y (PVY). The responses of the Ny-1 allele in the Rywal potato cultivar and transgenic NahG-Rywal potato plants that do not accumulate SA were characterized at the cytological, biochemical, transcriptome, and proteome levels. Analysis of noninoculated and inoculated leaves revealed that HR lesions started to develop from 3 d post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 69 publications
4
147
0
4
Order By: Relevance
“…A positive correlation between SA and GA, and negative feedback between JA/ET and GA in potato after PVY infection was shown previously (Baebler et al . ). A possible mechanism for this action suggested for Arabidopsis is via the DELLA proteins, which are growth repressor proteins that are degraded by a GA‐dependent mechanism (Navarro et al .…”
Section: Discussionmentioning
confidence: 97%
“…A positive correlation between SA and GA, and negative feedback between JA/ET and GA in potato after PVY infection was shown previously (Baebler et al . ). A possible mechanism for this action suggested for Arabidopsis is via the DELLA proteins, which are growth repressor proteins that are degraded by a GA‐dependent mechanism (Navarro et al .…”
Section: Discussionmentioning
confidence: 97%
“…In response to PVY infection, SA is synthesised de novo. The whole transcriptome analysis confirmed the central role of SA in orchestrating Ny-1-mediated responses and showed that the absence of SA leads to significant changes at the transcriptome level, including a delay in activation of expression of genes known to participate in defence responses (Baebler et al, 2014).…”
Section: Effects Of Viruses On Potato Gene Expressionmentioning
confidence: 65%
“…The lack of SA accumulation in the NahG potato plants (transgenic lines deficient in SA accumulation) causes unrestricted viral spreading and consequent disease symptoms (Baebler et al, 2014). Transcriptomic analysis confirmed the central role of SA in inducing the Ny-1-mediated responses and showed that the absence of SA leads to significant changes at the gene expression level, including a delay in activation of defence genes.…”
Section: Hormone-mediated Antiviral Defencesmentioning
confidence: 92%
“…The SA defence response is also triggered by Potato virus Y (PVY) and Tomato ringspot virus (ToRSV) (Jovel et al, 2011;Baebler et al, 2014). The lack of SA accumulation in the NahG potato plants (transgenic lines deficient in SA accumulation) causes unrestricted viral spreading and consequent disease symptoms (Baebler et al, 2014).…”
Section: Hormone-mediated Antiviral Defencesmentioning
confidence: 99%